The Effectiveness of Green Scallop Shell Chitosan as Coagulant in Treatment of Tofu Industrial Liquid Waste - Fauziah, Nurlaili; Ain, Ma'rifatul; Dewati, Retno (Universitas PGRI Madiun, 2022)
Tofu waste is gotten after processing soybean, and this waste contains a lot of polluting substances, hence it can pollute rivers and cause health problems. Meanwhile, one method used for treating wastewater into clean water is called the jartest method and its processes include coagulation-flocculation and deposition. This study aims to determine the effectiveness of green mussel shells as coagulants in the treatment of tofu industrial liquid waste. The variables used were 100 mesh green mussel shell powder, 1000 mL of liquid tofu dregs, 150 rpm fast stirring speed for 2 minutes, and 60 rpm slow stirring speed for 15 minutes. Furthermore, chitosan was used with different weight variations in grams (0.5, 0.7, 0.9, 1.1, and 1.3) as well as precipitation time with variations in minutes (20, 30, 40, 50, and 60). The content of Chitosan water was 1.29% and its degree of deacetylation was 65.04%. The result of the preliminary analysis of tofu liquid waste with a coagulant showed BOD, COD, and TSS levels of 965.25mg/L, 435mg/L, and 395mg/L with pH 4 respectively. However, these levels were changed to 195.56mg / L; 299mg/L; and 195.32 mg/L with pH 6 after the final analysis of the liquid waste was conducted.